2008
DOI: 10.1002/jmri.21297
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural abnormalities in children with spina bifida myelomeningocele and hydrocephalus: A diffusion tensor tractography study of the association pathways

Abstract: Purpose:To quantify microstructural abnormalities in the major association pathways of children affected by spina bifida myelomeningocele (SBM) and shunted hydrocephalus using whole-brain diffusion tensor imaging (DTI). Materials and Methods:The institutional review board approved this Health Insurance Portability and Accountability Act (HIPAA)-compliant study and written informed consent/assent were obtained prior to the study. The 69 participants included 38 children with SBM and shunted hydrocephalus (age m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 36 publications
(85 reference statements)
6
83
1
Order By: Relevance
“…Although Assaf et al 14 studied abnormal anisotropic diffusion properties in various WM regions before and after CSF shunt surgery, they did not include patients in early childhood, the common age of hydrocephalus presentation and treatment. In a similar fashion, in a recent DTI study by Hasan et al 15 of children with spina bifida and hydrocephalus, the average age of participants was 12.3 Ϯ 2.1 years, well beyond the usual age of diagnosis and treatment of childhood hydrocephalus.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Although Assaf et al 14 studied abnormal anisotropic diffusion properties in various WM regions before and after CSF shunt surgery, they did not include patients in early childhood, the common age of hydrocephalus presentation and treatment. In a similar fashion, in a recent DTI study by Hasan et al 15 of children with spina bifida and hydrocephalus, the average age of participants was 12.3 Ϯ 2.1 years, well beyond the usual age of diagnosis and treatment of childhood hydrocephalus.…”
mentioning
confidence: 63%
“…Previously published reports have used DTI to examine the effects of hydrocephalus on WM in older children or in young adults. 14,15 In our study, the study population ranged from ages 1 day to 16 months at the time of the pretreatment MR imaging/DTI study. Thus, it fills a knowledge gap and provides a radiographic reflection of the understanding for the effects of hy Fig 3.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced FA and higher diffusivity have also been found in the major associative pathways of the supratentorial white matter tract in patients with Chiari II and are thought to reflect altered development and/or effects of chronic hydrocephalus on myelination, cell membrane integrity, and stretching of fibers. 9,10 Therefore, our findings may indeed reflect altered neuronal cell or fiber packing or organization in the context of abnormal cerebellar development. Our findings are also consistent in that the ADC values of the pons were not significantly different from those in healthy controls.…”
Section: Discussionmentioning
confidence: 84%
“…To corroborate this thesis, they performed diffusion tensor tractography to delineate and quantify bilaterally four major association pathways (arcuate, inferior longitudinal, inferior fronto-occipital, and uncinate fasciculi) of the patient with spina bifida meningomyelocele (SBM); and they showed that these patients have abnormal development, impairment in myelination as well as abnormalities in intrinsic axonal characteristics and extra-axonal/ extracellular space in their association pathways. At the end of this study they hypothesized that the differences in the diffusion metrics observed in the children with SBM are suggestive of abnormal white matter development and persistent degeneration with increased age 9,10) . On the other hand, there are few data on the adult hydrocephalus without SBM.…”
Section: Discussionmentioning
confidence: 99%